Гомолиз алкоксиаминов как удобный инструмент в исследованиях механизма плазмон-активируемых реакций - Воткина Д. Е.; Горбунова А.; Гусельникова О. А.; Петунин П. В. Павел Васильевич; Марк С.; Постников П. С. Павел Сергеевич (2025, 2025)
Текстовый файл